Flexible Ferroelectric Materials-Based Triboelectric Nanogenerators for Mechanical Energy Harvesting - Dan, Huiyu; Li, Hongyu; Yang, Ya (Frontiers in Materials, 2022)
Triboelectric nanogenerators are widely used in a variety of applications including wearable electronics, self-driven sensors, electrochemistry, and other fields. A lot of work has been done by researchers to increase the performance of triboelectric nanogenerators. Changing device structure, physical surface engineering and chemical composition modification are common effective methods. Some recent studies have found that the polarization of ferroelectric materials can regulate the output of triboelectric nanogenerators. Compared with other materials, ferroelectric materials have the advantages of polarization characteristics and large dielectric constant, which can improve the output performance by regulating the electric potential on the surface of the material, and can also collect the pyroelectric -piezoelectric-triboelectric coupling energy. However, most ferroelectric materials are rigid and therefore difficult to apply to flexible wearable electronics. In this paper, we briefly describe the mechanism of ferroelectric polarization boosts triboelectric output and the working mechanism of coupled generators, then introduce some flexible ferroelectric materials and finally introduce some of their recent applications